Dynamics of Prolactin Axis Genes in the Brain of Male and Female Three-spined Stickleback Gasterosteus aculeatus (Gasterostaidae) during Short-Term Freshwater Adaptation - Pavlova, N. S.; Neretina, Tatiana Vladimirovna; Smirnova, Olga V. (Journal of Ichthyology, 2020)
Abstract: Expression of prolactin axis genes (prolactin Prl1, prolactin-like hormone Prl2, prolactin receptor “a” PrlRa, and prolactin receptor “b” PrlRb) have been studied in the brains of females and males of the three-spined stickleback Gasterosteus aculeatus upon adaptation to fresh water. The expression of the Prl1 gene in females was significantly higher after 24-h adaptation to the freshwater relative to the control group (seawater) and to that in males at the same time point. No changes in Prl2 gene expression in females and Prl1 in males were detected. In males, after 12 and 18 h of adaptation to fresh water, higher expression of the Prl2 gene was observed relative to the control group. The expression of the PrlRa gene in males in seawater is higher than that in females; upon adaptation to fresh water, it does not change in females, and it decreases in males gradually after 3 h of being transferred to fresh water. No differences in the expression of the PrlRb gene between females and males in seawater were detected; however, after 24 h of freshwater adaptation, this parameter was higher in females than in males. Changes in the expression of prolactin axis elements during freshwater adaptation are gender-dependent, and the contribution of prolactin and prolactin-like hormone to adaptation of females and males of the three-spined stickleback to fresh water is significantly different.
CRIS-Team Scopus Importer:2023-04-20
Keywords: freshwater adaptation; osmoregulation; prolactin; prolactin receptor; prolactin-like hormone; three-spined stickleback Gasterosteus aculeatus